The Effect Of Work From Home, Work Discipline And Incentive Giving On Employee Performance At Pt. Astra Internasional, Tbk–Isuzu Medan - Kristanty M N Nadapdap; Siti Normi Sinurat; Sondang N B Marbun; Junika Napitupulu; Marsella Peranginangin (Manajemen: Jurnal Ekonomi, 2024)
This study aims to determine the effect of work from home, work discipline and incentives on employee performance at PT. Astra Internasional, Tbk - Isuzu Medan. This type of research uses quantitative research. The number of samples in this study was 37 respondents. Based on the results of the t hypothesis test, it can be concluded that work from home has a positive and significant effect on employee performance, with a tcount value of 2.769> ttable 2.036 and a sig value of 0.009 <0.05, work discipline has a positive and significant effect on employee performance, with a tcount value of 2.205> ttable 2.036 and a sig value of 0.035 < 0.05, and incentives have a positive and significant effect on employee performance, with a tcount value of 2.428> ttable 2.036 and a sig value of 0.021 <0.05. Based on the results of the F hypothesis test, it can be concluded that simultaneously work from home, work discipline and incentive provision have a positive and significant effect on employee performance, with the Fcount value> Ftable, which is 13,369> 2.89 and the significance value F < significance value (0.000 <0.05). Based on the results of the R2 test, it can be concluded that the R2 value is 0.549 (54.9%) which means that the variation in employee performance values ​​is determined by the role of variations in work from home values, work discipline and incentive provision